Perancangan Pesantren Mualaf Pekanbaru Pendekatan Arsitektur Islam - Ilham Gusriyadi; Repi Repi; Rika Cheris (JURNAL TEKNIK UNILAK, 2020)
Islamic Boarding School is a traditional educational institution, teaches various things about Islam, in contrast to Islamic boarding schools in general, the Islamic Boarding School for Muslims is specifically intended for Converts, namely for people who have recently joined Islam. Islamic Boarding School guides Converts in learning everything about Islam, namely in the field of guidance and education in the form of the Aqeedah, akhlaq, tauhid, reading the Qur'an, Fiqh, Tafsir and Arabic. The design is intended so that Converts feel the presence of brothers and sisters who can help strengthen their Islamic beliefs and boarding schools as a place or home for them so they can feel a peaceful Islam. Pekanbaru Islamic Boarding School can be a national and international Islamic educational institution and an attraction of the city of Pekanbaru, known as the city of Madani in Islam and in harmony with the Malay culture that is characterized by a strong Islamic. Comfort in learning for converts is very important to be able to focus on studying Islamic religion. The design of Islamic boarding schools uses qualitative research methods to obtain primary and secondary data, literature studies, empirical studies and interviews related to the concept of Islamic Architecture approach in Islamic Boarding Schools. The application of Islamic boarding school design conceptualizing the Islamic Architecture approach to the application on the outside and inside the building in the form of ornaments that reminds Allah SWT, setting the space to maintain akhlaq and make it easier of students activity.